TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DAN PELAYANAN BALI BAKERY - Kadalora, Eka; Wiranatha, A.A.P.Agung Suryawan; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The aim of this study are 1) To find out the attributes that are considered important by consumers in order to achieve the consumer satisfaction of Bali Bakery 2) To determine the level of c onsu me r’s satisfaction on the products and services provided by Bali Bakery 3) To determine the attributes that considered to get priority in Bali Bakery, based on the level of suitability between interests and performance to provide the satisfaction to the consumers. The data of this study was obtained by distributing 187 questionnaires to the consumers of Bali Bakery Hayam Wuruk Denpasar branch. The Importance Performance Analysis method was used to determine the level of c onsumer satisfaction related to product quality and service quality performed by the company . The results of the study indicate that consumers were satisfied toward the quality of the product and the quality of services provided by the company. The level of c onsu mer satisfaction toward the product quality was 80,34% and toward the service quality was 81.27%. The attributes that need to be prioritized were all of variables in quadrant A, namely affordable product prices, product packaging that was able to keep the product from being damaged to its destination, the availability of adequate parking space , employees of Bali Bakery provid ing the same service regardless of social status, and the Bali Bakery restaurant established the opening hours in accordance to the needs of consumers. Keywords: Consumer Satisfaction, Im portance P erformance A nalysis, C artesian D iagram.